Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s11414-007-9087-x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Qualitative Methods in Systems of Care Research

Abstract: In an effort to understand the impact of qualitative methods on the field of children's mental health, a review of the proceedings of the University of South Florida's Research and Training Center for Children's Mental Health (RTC) conferences from 1988 through 2003 was conducted. One hundred presentations published in the proceedings were identified as meeting criteria for inclusion as qualitative research. Data regarding title, topic, researchers, funders, methodology, and results were collected and reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…For instance, a published review of all of the qualitative research presented at one of the leading system of care research conferences (the University of South Florida’s Research and Training Center for Children’s Mental Health) from 1988 to 2003 did not mention the rural context as an issue or topic of research (Hodges, Hernandez, Pinto, & Uzzell, 2007). An additional review, conducted by the present authors, of the conference proceedings from this conference between 2003 to 2007 found only three presentations that specifically addressed the rural context (Dean, Wiens, Liss, & Stein, 2007; Gilford & Walrath, 2008; Thomlinson, Maples, & Rimel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a published review of all of the qualitative research presented at one of the leading system of care research conferences (the University of South Florida’s Research and Training Center for Children’s Mental Health) from 1988 to 2003 did not mention the rural context as an issue or topic of research (Hodges, Hernandez, Pinto, & Uzzell, 2007). An additional review, conducted by the present authors, of the conference proceedings from this conference between 2003 to 2007 found only three presentations that specifically addressed the rural context (Dean, Wiens, Liss, & Stein, 2007; Gilford & Walrath, 2008; Thomlinson, Maples, & Rimel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, clear evidence of a spreading qualitative research movement appears in virtually every practice area where it has encompassed researchers, faculty, and students of all stripes. Scholarly articles tracking this ''tectonic change'' (O'Neill, 2002, p. 190) have appeared in the full range of professional areas including industrial-organizational (Cassell & Symon, 2006), counseling (Hoyt & Bhati, 2007), educational (Butler, 2006;Shank, 1994), school (Michell, 2004), health (Dickson-Swift, James, Kippen, & Liamputtong, 2007;Hodges, Hernandez, Pinto, & Uzzell, 2007;Yardley, 2000), clinical child (Krahn, Holn, & Kime, 1995), community (Bayard & Miller, 1998), evaluation (Mark, 2002), sport and exercise (Weinberg & Gould, 2007), and general professional psychology (Goldman, 1993).…”
Section: Challenges Of Professional Practice: Presence Of Social Prob...mentioning
confidence: 99%
“…This change has been documented across all areas of psychology, including counseling (Hoyt & Bhati 2007), health (Hodges et al 2007), school (Michell 2004), clinical (Rennie, Watson & Monteiro 2002), evaluation (Mark 2002), sport and exercise (Weinberg & Gould 2007) and industrial-organizational (Cassell & Symon 2006). The last two decades have seen an explosion of volumes on qualitative methods in the social sciences (e.g., Brewer & Hunter 1989;Cresswell 1998;Denzin & Lincoln 2000Taylor & Bogdan 1998), including many specifically addressing the utility of these methods for psychological research (e.g., Camic, Rhodes & Yardley 2003;Kopala & Suzuki 1999;McLeod 2001).…”
mentioning
confidence: 96%